PERLINDUNGAN HUKUM TENAGA KERJA INDONESIA OLEH DINAS TENAGA KERJA TRANSMIGRASI DAN KEPENDUDUKAN JAWA TIMUR (Studi Deportasi Tenaga Kerja Indonesia Dari Malaysia) - , JUWARIYAH, Dr. Ari Hermawan ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research entitled Legal Protection of Indonesian Workers by Department of Labor Employment, Population and Transmigration. (Study of Indonesian Labor Deports from Malaysia) aims to determine the factors that led to Labor Indonesia from East Java who became an undocumented status so that the deportees from Malaysia, and protection of labor laws by the Indonesian Labor Department of Employment, Population and Transmigration of East Java. This study is an empirical legal research, research that focuses on the data of field research (field research) in order to obtain primary data. Research literature (library research) is also performed to support the primary data. Sampling was carried out by Non Probably sampling techniques, namely the selection of the sample by ignoring the principles of probability and not a random sample selection. Data analysis techniques used in this study are a qualitative analysis. Data are presented with descriptive method. The results showed that the factors that cause workers from East Java Indonesia to the status of undocumented (illegal) so that the deportees from Malaysia, are: workers terminated for no apparent reason, workers return because the job is too heavy and / or a lot, workers laid off because the employer / company suffered bankruptcy / bankruptcy, workers inexpedient with the employer, sickness workers, do not have documents, passports and work permits. Protection of Indonesian Workers by Department of Labor Employment, Population and Transmigration of East Java Population is not maximized, post-placement Empowerment of workers in quality and quantity monitoring still needs improvement, especially after training. Another problem is the content and training methodology that still uses a participatory approach to formal and not so many participants are still less when implemented in the field.